EMBRYONIC AND LARVAL DEVELOPMENT OF THE PRAWN MACROBRACHIUM KISTNENSIS - Nagabhushanam, R; Kulkarni, M Y (Indian Journal of Fisheries, 2011)
The embryonic and larval development of Macrobrachium kistnemis is described in detail. The larvae were reared in the laboratory, These were liberated by ovigerous females on the twentyninth day during night. The period of embryonic development was found to be 29 to 30 days. Four zoaeal stages and the postlarval are described and illustrated. The larval development was complete in the laboratory and the larva entered into the juvenile adult condition in 7-11 days after hatching. The duration of the various zoaeal stages varied between 24 h and four days, and the average period was 3-2 days.